Colorectal cancer risk variant rs7017386 modulates two oncogenic lncRNAs expression via ATF1-mediated long-range chromatin loop. (10th October 2021) - Wang, Haoxue; Zhu, Ying; Chen, Hongda; Yang, Nan; Wang, Xiaoyang; Li, Bin; Ying, Pingting; He, Heng; Cai, Yimin; Zhang, Ming; Niu, Siyuan; Li, Yue; et al.
Abstract: The activating transcription factor 1 (ATF1) has been identified as a vital pathogenic factor in the progression of colorectal cancer (CRC), whiles, the precise regulatory mechanisms remain elusive. Here, we comprehensively characterized the ATF1 cistrome by RNA-seq and ChIP-seq assays in CRC cell lines. As the results, we identified 358 genes differentially regulated and 15, 029 ATF1 binding sites and demonstrated that ATF1 was widely involved in major signaling pathways in CRC, such as Wnt, TNF, Jak-STAT. Subsequently, by the expression quantitative trait loci (eQTL) analyses, we found that rs7017386 was associated with the expression of CCAT1 and PVT1 in the Wnt pathway. By a two-stage population study with 6, 131 CRC cases and 10, 022 healthy controls, we identified the variant was associated with CRC risk. Mechanistically, we found rs7017386 allele-specifically enhanced the binding affinity of ATF1 and promoted the expressions of PVT1 and CCAT1, via forming a long-range chromatin loop. Moreover, those two lncRNAs could synergistically facilitate c-Myc expression to activate the Wnt pathway in CRC progression. Our findings not only demonstrated the transcriptomic profiling of ATF1 in CRC, but also provided important clues for the etiology of CRC. Highlights: ● The ATF1 cistrome were characterized in CRC cells via RNA-seq and ChIP-seq assays. ● ATF1 is widely involved in signaling pathways in CRC, such as Wnt, TNF, Jak-STAT. ● The rs7017386 variant is significantly associated with CRC risk. ● The rs7017386 promotes the expressions of PVT1 and CCAT1 via long-range loop. ● PVT1 and CCAT1 synergistically facilitate c-Myc expression to activate Wnt pathway.